2018
DOI: 10.1186/s13071-018-2883-8
|View full text |Cite
|
Sign up to set email alerts
|

A high-risk Zika and dengue transmission hub: virus detections in mosquitoes at a Brazilian university campus

Abstract: BackgroundZika virus (ZIKV) and dengue virus (DENV) are mosquito-borne flaviviruses prevalent throughout tropical regions. Currently, management of ZIKV and DENV centers on control of the primary vector Aedes aegypti. This vector is highly anthropophilic and is therefore prevalent throughout densely urbanised landscapes. A new passive trap for gravid Ae. aegypti (Gravid Aedes Trap - GAT) was developed for mosquito surveillance. Here the different killing agents and the level of transmission of arboviruses that… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
16
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(17 citation statements)
references
References 38 publications
0
16
0
1
Order By: Relevance
“…In Belo Horizonte, Brazil, both DENV and ZIKV were detected in Ae. aegypti collected at a university 32 . Furthermore, La Crosse virus was detected in Aedes triseriatus in cemeteries in Tennessee, USA 33 .…”
Section: Discussionmentioning
confidence: 93%
“…In Belo Horizonte, Brazil, both DENV and ZIKV were detected in Ae. aegypti collected at a university 32 . Furthermore, La Crosse virus was detected in Aedes triseriatus in cemeteries in Tennessee, USA 33 .…”
Section: Discussionmentioning
confidence: 93%
“…This is corroborated by Baak-Baak et al 23 , who found 1.2% (2/166) positivity for dengue virus in churches. Meanwhile, in Belo Horizonte, the State capital of Minas Gerais, Eiras et al 24 found 4.9% (4/82 pools) and 8.5% (7/82 pools) infectivity to dengue virus and Zika virus, respectively, at the university Moreover, the possibility of transovarian transmission of dengue 25 , chikungunya 26 and Zika 27,28 in Ae. aegypti shows that a varied percentage of mosquitoes can be infected with these viruses.…”
Section: Discussionmentioning
confidence: 99%
“…We failed to isolate the virus and to perform whole genome sequencing. The infection rate of 0.5% in mosquitoes we have obtained is lower than what could be estimated during an epidemic [29]. However this screening method can be used as a passive surveillance system alerting of any increase in infection rates in mosquitoes, sign of an imminent epidemic.…”
Section: Discussionmentioning
confidence: 50%